Workplace Self-Care Networks in The Literature From 2019 To 2022 - GarcÃa Lirios, Cruz (The International Journal of Accounting and Business Society, 2022)
Purpose — The document explores the literature published from 2019 to 2022 regarding occupational self-care. It proposes that the risks and contagion, illness, and death reduced the accidents and illnesses in the local occupational field. Design/methodology/approach—A documentary, cross-sectional, exploratory, and correlational study was conducted using a sample of findings published in journals indexed to international repositories, considering the keywords "self-care" and "COVID-19" from 2019 to 2022. Findings — A structure of neural networks was found that reflects learning from the literature regarding the intensification of information related to the pandemic, infections, diseases, and deaths in the workplace. Practical implications — The findings allow the design of a workplace communication and risk prevention policy. Such guidelines correspond to biosafety policies in organizations in case of contingencies. Originality/value — The study's contribution to the state of the matter lies in establishing a research agenda on occupational health and self-care in the face of health crises, risks, and contingencies. Paper type — Case study